Using the Theory of Planned Behaviour when designing motivational letters: Exploring through patient interviews how determinants of behaviour are operationalised in letters of invitation to cardiac rehabilitation - Corinna Dressler (Tehran University of Medical Sciences, 2018)
Background & Aim: While health behaviour theories are often used to develop written material for health care interventions, descriptions of how to operationalise such theories are lacking in the literature. Paradoxically, it is precisely this information that is supposed to influence patient behaviour. Letters inviting patients to participate in cardiac rehabilitation are further examined here. Materials & Methods: Semi-structured interviews were conducted to explore how concepts from the Theory of Planned Behaviour had been operationalised in invitation letters, focusing on the motivational potential of different passages. Results: Thirteen participants were interviewed and asked to comment on the invitation letters. Without having been informed about the Theory of Planned Behaviour, most commented on passages that were based on the theory. It seemed important to many participants that the content is more relatable and personal. Message framing and the use of the future tense in sentences meant to motivate patients to attend cardiac rehabilitation appeared to be important. Using simple language might be more effective than technical terms. Conclusion: When using health behaviour theories such as the Theory of Planned Behaviour to compose materials motivating patients to behave in certain ways, message framing and relatable content are approaches to operationalizing theoretical concepts.